2008
DOI: 10.1161/hypertensionaha.108.118273
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High-Normal Blood Pressure on the Risk of Cardiovascular Disease in a Japanese Urban Cohort

Abstract: Abstract-Few prospective studies have examined the association between high-normal blood pressure and cardiovascular disease (CVD) in Asia. We examined the impact of high-normal blood pressure on the incidence of CVD in a general urban population cohort in Japan. We studied 5494 Japanese individuals (ages 30 to 79 years without CVD at baseline) after completing a baseline survey who received follow-up through

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 153 publications
(137 citation statements)
references
References 34 publications
5
130
1
1
Order By: Relevance
“…The assumptions required for proportional hazards were met, and these were assessed with graphs of log-log plots. Population-attributable fraction (PAF) [30,31] was calculated using the formula: PAF=pd [(HR−1)/HR], in which pd was the proportion of individuals exposed to a risk e AUCs for insulin and glucose were calculated during the first 30 min of the OGTT using the trapezoidal method factor and HR was the adjusted HR [32]. Multivariableadjusted HRs and 95% CIs for type 2 diabetes incidence according to major risk factors for diabetes were calculated using Cox proportional hazards regression in the normal, i-IIS, i-IR, and IIS plus IR groups.…”
Section: Discussionmentioning
confidence: 99%
“…The assumptions required for proportional hazards were met, and these were assessed with graphs of log-log plots. Population-attributable fraction (PAF) [30,31] was calculated using the formula: PAF=pd [(HR−1)/HR], in which pd was the proportion of individuals exposed to a risk e AUCs for insulin and glucose were calculated during the first 30 min of the OGTT using the trapezoidal method factor and HR was the adjusted HR [32]. Multivariableadjusted HRs and 95% CIs for type 2 diabetes incidence according to major risk factors for diabetes were calculated using Cox proportional hazards regression in the normal, i-IIS, i-IR, and IIS plus IR groups.…”
Section: Discussionmentioning
confidence: 99%
“…26 Moreover, our findings suggested that stroke risk of subjects with prehypertension in their 50s, but not for such subjects in their 40s, was similar to that of normotensive subjects. Recent studies about relationship between elevated BP and PAF for stroke incidence of Japanese in the Japan Public Health Centre study 27 and the Circulatory Risk in Communities Study 28 suggested that the 29 Those controversial issues regarding prehypertension impact on stroke events could be because of white coat hypertension and the potential impact of fluctuations in BP levels after midlife that may affect stroke incidence. Further analysis of the relation between BP fluctuation and stroke could shed light on the issue whether early BP control over normal levels at midlife could be beneficial for prevention of stroke incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 6485 males and females underwent regular health checkups between September 1989 and March 1994. The subjects have continued to visit the National Cerebral and Cardiovascular Center (NCVC) every two years for regular health checkups [21][22][23][24] . A total of 1,546 subjects were excluded from the study based on a past history of CHD or stroke, non-fasting blood collections, missing data or because they were lost to follow-up.…”
Section: Populationsmentioning
confidence: 99%
“…The follow-up method used in the Suita study has been reported previously [20][21][22][23][24] . The endpoints for the current follow-up study were: (1) the date of the first diagnosis of CHD (2) the date of death, (3) the date when the subject left Suita or (4) censoring by December 31, 2007.…”
Section: Endpoint Determinationmentioning
confidence: 99%